THE EUROPEAN LANGUAGE PORTFOLIO: TIME FOR A FRESH START? - David Little (Informascope, 2016)
This article is based on the plenary talk I gave at the 2016 GlobELT Conference (Antalya, 14-17 April). I begin by reminding readers of the structure of the ELP and pointing out that although it was greeted with enthusiasm in most Council of Europe member states, it is not widely used in most of them (Turkey and Albania are current exceptions to this general tendency). I then elaborate on the relation between the ELP and the CEFR and sketch the ELP's history from 1998 to 2014. After that I offer answers to two questions: Why has the ELP been a relative failure in most countries? And why did the ELP succeed in Ireland with learners from immigrant backgrounds? Finally, I consider how we might make a fresh start